2022
DOI: 10.1101/2022.06.20.496822
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ex vivoExpansion Potential of Murine Hematopoietic Stem Cells: A Rare Property Only Partially Predicted by Phenotype

Abstract: Hematopoietic stem cells (HSCs) reside at the apex of hematopoiesis, can maintain this function for life, and are the functional units in clinical bone marrow transplantation. The limited HSC numbers not only restricts their clinical use but also several embodiments of experimental research. Recently, a highly defined ex vivo culture system was shown to support several hundredfold expansion of functional in vivo HSC activity. Here, we further explored this system. Over a 3-week culture period, only 0.1% of ini… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Next, we leveraged LARRY barcoding to assess the clonal dynamics and cell fate choices of expanded HSCs over time. We found that expansion cultures gradually lose their clonality, despite initiating from highly pure EPCR+ HSCs, in line with recent reports (Figure 1D) (Zhang et al 2024). Sister-cell splitting across independent wells confirmed the preferential expansion of specific clones, which correlated across wells higher than expected based on a null distribution obtained from a sampling simulation (Figure 1D).…”
Section: Pva-based Expansion Cultures Maintain Heterogeneous and Dete...supporting
confidence: 91%
“…Next, we leveraged LARRY barcoding to assess the clonal dynamics and cell fate choices of expanded HSCs over time. We found that expansion cultures gradually lose their clonality, despite initiating from highly pure EPCR+ HSCs, in line with recent reports (Figure 1D) (Zhang et al 2024). Sister-cell splitting across independent wells confirmed the preferential expansion of specific clones, which correlated across wells higher than expected based on a null distribution obtained from a sampling simulation (Figure 1D).…”
Section: Pva-based Expansion Cultures Maintain Heterogeneous and Dete...supporting
confidence: 91%
“…We and others have previously established the e cacy of a polyvinyl alcohol (PVA)-based culture system in promoting murine HSC expansion. Notably, expanded HSCs enable a degree of HSC-derived reconstitution even in completely unconditioned hosts 11,12 . Given this, we explored the impact of larger quantities of HSCs on in vivo reconstitution outcomes in both non-conditioned and alternatively conditioned hosts.…”
Section: Ex Vivo Expanded Hscs Effectively Reconstitute Multilineage ...mentioning
confidence: 99%
“…Cells from primary recipients were pooled before transplantation. For in vivo proliferation tracking, cultured cells and CD4-enriched splenocytes isolated from C57BL/6-CD45.1 or C57BL/6-CD45.2 mice were labeled with CTV dye as previously described 12 . EE100 HSCs were cotransplanted with 2x10 6 splenocytes into each C57BL/6-CD45.2 or C57BL/6-CD45.1/CD45.2 unconditioned or CD45-SAP treated recipient.…”
Section: Transplantationmentioning
confidence: 99%
See 1 more Smart Citation